2016
DOI: 10.5498/wjp.v6.i2.269
|View full text |Cite
|
Sign up to set email alerts
|

Review of key telepsychiatry outcomes

Abstract: AIM:To conduct a review of the telepsychiatry literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
416
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 430 publications
(434 citation statements)
references
References 123 publications
12
416
1
5
Order By: Relevance
“…Similarly, an evaluation by the US National Institute of Justice found that virtual care more generally (including synchronous and asynchronous care) has specific value for defined patient populations, reducing external visits to specialists and costly off-site transfers for care of prisoners [37] and providing a cost-effective solution for patients with limited access to mental health services [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, an evaluation by the US National Institute of Justice found that virtual care more generally (including synchronous and asynchronous care) has specific value for defined patient populations, reducing external visits to specialists and costly off-site transfers for care of prisoners [37] and providing a cost-effective solution for patients with limited access to mental health services [38]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, inpatient interdisciplinary treatment team meetings, which typically include physicians, nurses, and social workers, can be reformatted to videoconference. In contrast, use of telepsychiatry is more well-suited for outpatient encounters, with outcomes being comparable to in-person care (Hubley et al 2016), though there may be some circumstances where an in-person visit, despite the risk of exposure, may be warranted-as in worsening mental illness requiring a higher level of care.…”
mentioning
confidence: 99%
“…Notes 1 See also Hubley et al (2016) for a review of trials which foregrounds the import of access. 2 See: http://www.mindtech.org.uk.…”
Section: Resultsmentioning
confidence: 99%